The Construction of Island Islamic Traditions: A Phenomenological Study of the Prophet's Birthday Tradition Sacredness on Bawean Island - Saniri, Saniri; Yakin, Ainul; Amaliati, Siti (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The tradition of the Prophet's Birthday on Bawean Island embodies the intersection of Islamic values ​​and local culture, shaping the distinctive religious practices of the island's people. This tradition is a religious celebration and a means of preserving cultural identity. This study formulates two main questions: (1) How is the sacred construction of the Prophet's Birthday tradition in Bawean formed through the interaction of Islam and local culture? Moreover, (2) How do people across generations interpret this tradition? The study used a qualitative approach with Husserl's phenomenology to explore the community's religious experiences. Data were collected through in-depth interviews, participant observation, and documentation in the form of archives, prayers, and photographs of the procession. Informants were selected purposively, including religious leaders, cultural figures, the Maulid committee, the general public, and the younger generation. Data analysis used phenomenological stages: bracketing, intuiting, analyzing, and describing. The findings indicate that the sacredness of the Maulid in Bawean is understood as a space for strengthening faith, social solidarity, and cultural inheritance. This tradition represents a harmonious construction of archipelagic Islam: Islamic in its values, local in its expression, and sacred in the spiritual experience of its people.